The Impact of ESG Regulations and Taxonomy on the Credit Process in Commercial Banks - Kosztowniak, Aneta (Journal of Finance and Financial Law, 2024)
The purpose of the article is to present the impact of legal regulations in the field of sustainable development (ESG) and taxonomies on the course of credit processes in commercial banks. Methodology refers to studies of legal regulations, comparative analysis of cases (case study) and inference. Results of the research show that the implementation of ESG regulations and taxonomies and the adaptation of credit processes in commercial banks will result in structural changes in loan portfolios in the near future while moving away from financing dirty industries towards the green ones. As a result, the financing stream for green assets and those supporting sustainable development will be increased, while the financing of dirty assets will be significantly reduced due to the increase in risks and accompanying costs for customers and banks. It is expected that even if some banks grant loans to finance dirty assets, they will only be short-term loans and will require high servicing costs (commission, margin, legal security, and insurance). This is due to the fact that the portfolio with credit exposures in the so-called dirty industries (mining, construction, trade) will escalate the increase in ESG risk. Such a portfolio with dirty exposures will require banks to secure additional reserve capital to maintain higher general and sector systemic risk buffers. Some banks will completely stop financing assets from dirty industries, which will mean that some of them will be abandoned due to the lack or high costs of their modernization, intensifying the negative socio-economic consequences. The ongoing process of redirecting the financing stream to green assets in banks means that enterprises and households need to take earlier adaptation actions. These include actions against financing constraints in dirty sectors and likely future losses in infrastructure and assets related to them.